2015
DOI: 10.1002/wrna.1310
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐based regulation of transposon expression

Abstract: Throughout the domains of life, transposon activity represents a serious threat to genome integrity and evolution has realized different molecular mechanisms that aim to inhibit the transposition of mobile DNA. Small noncoding RNAs that function as guides for Argonaute effector proteins represent a key feature of so-called RNA interference (RNAi) pathways and specialized RNAi pathways exist to repress transposon activity on the transcriptional and posttranscriptional level. Transposon transcription can be dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 200 publications
(226 reference statements)
3
29
0
1
Order By: Relevance
“…2). This is consistent with most models of endo-siRNA and piRNA biogenesis in bilaterians in which some endo-siRNAs are cleaved from secondarily structured primary transcripts while piRNAs are not [53]. Given that the putative piRNA and endo-siRNA clusters identified here have proven to be consistent with previously reported properties, we deemed our method to be satis-factory for naive identification and annotation.…”
Section: Discrimination and Annotation Of Rnai Classes In Drosophilasupporting
confidence: 88%
See 1 more Smart Citation
“…2). This is consistent with most models of endo-siRNA and piRNA biogenesis in bilaterians in which some endo-siRNAs are cleaved from secondarily structured primary transcripts while piRNAs are not [53]. Given that the putative piRNA and endo-siRNA clusters identified here have proven to be consistent with previously reported properties, we deemed our method to be satis-factory for naive identification and annotation.…”
Section: Discrimination and Annotation Of Rnai Classes In Drosophilasupporting
confidence: 88%
“…As anticipated, multi-mapping endo-siRNAs and piRNAs derive primarily from transposons ( Fig. 1) [53,54]. In addition, we found that unique endo-siRNA clusters frequently map to exons, 5' and 3' UTRs in coding genes ( Fig.…”
Section: Discrimination and Annotation Of Rnai Classes In Drosophilasupporting
confidence: 76%
“…Faced with the grave threat posed by active TEs, animals employ germline-expressed PIWI proteins and PIWI-interacting (pi-) RNAs to suppress TE activity on the transcriptional and post-transcriptional level, thus ensuring the transmission of intact genomes from one generation to another [24]. We have recently shown that shifts in temperature from 18 C to 29 C not only alter the expression level of specific TEs in Drosophila melanogaster, but also lead to a more pronounced PIWI/piRNA response, presumably due to reduced back folding of TE transcripts, making them more accessible for piRNAguided PIWI attacks [4].…”
Section: Ii) Temperature and Transposon Propagation In Drosophila Evomentioning
confidence: 99%
“…Small non-coding (snc-) RNAs are important players in diverse cellular processes, often acting as guide molecules in transcriptional and post-transcriptional gene regulation [1,2,3]. Micro (mi-) RNAs, short interfering (si-) RNAs and Piwiinteracting (pi-) RNAs constitute their most prominent representatives but the number of described sncRNA classes continuously increases.…”
Section: Introductionmentioning
confidence: 99%